Basidiobolomycosis in Togo: clinico-pathological study of a series of 12 presumed cases - Darré, Tchin (BMC Res Notes, 2018)
OBJECTIVE: The purpose of our study was to describe the histological diagnosed of the Basidiobolomycosis cases from 1990 to 2017 (28 years) in the only Pathology Anatomy Laboratory in Togo. RESULTS: A total of 12 cases of suspected Basidiobolomycosis have been identified. The sex ratio (M/F) was 2. The average age of the patients was 24.8 ± 1.6 years. Six patients (6/12) had a pathological history: HIV infection (n = 4 cases) and tuberculosis (n = 2 cases). The clinical manifestations were localized to pure skin (n = 9 cases), skin and mucous digestive (n = 2 cases) and disseminated (n = 1 cases). Direct mycological examination and culture in 4 patients was positive in 3 patients. The samples examined consisted of 11 cutaneous biopsies measuring 1–3 cm and a biopsy of the intestinal mucosa. Histology showed granulomatous inflammation of the dermohypodermal site with numerous giant cells associated with eosinophilic polynuclear cells, in which there are 5–7 mm non-septate, irregular mycelial filaments. Patients were treated with ketoconazole at a dose of 10 mg/kg daily. The progression of the patients’ condition was favorable after 4 weeks of treatment with a regression of the closets size. Patients were completely healed after 8 weeks of treatment, without recurrence after 6 months. No deaths have been recorded.